Peran Mahasiswa Kuliah Kerja Nyata (KKN) Pada Kegiatan Asistensi Mengajar Sebagai Alternatif Pengembangan Jiwa Kewirausahaan Siswa Di SMKN 4 Kota Bima - Pratiwi, Aliah; Huda, Nurul; Ovriyadin; Selfania; Sagiratun, Safira (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2024)
Abstract Teaching Assistance is one of the programs from Merdeka Belajar Kampus Merdeka or known as MBKM. This program was opened with the aim of providing students with the opportunity to learn by developing themselves outside campus through Teaching Assistance in secondary school level education units under the guidance of field supervisors. The methodology for implementing Teaching Assistance carried out by KKN students at the Bima College of Economics at SMKN 4 Bima City is the preparation and implementation method. During the implementation of teaching assistance activities at SMKN 4 Bima City, assistance students have played a role and participated in various programs at the school. In the activity stage, students provide material about entrepreneurship so that students' understanding of entrepreneurship is more open, and this activity is also carried out in practical form, namely school students are taught how to create an innovative product by utilizing local potential, namely marine products. Apart from the product manufacturing process, students are also taught the product packaging process so that the product is suitable for marketing to consumers. Overall, the Teaching Assistance activities carried out by Bima College of Economics KKN students at Bima City Vocational School 4 went well.